Reckoning of facial grimacing scheme for patient agitation in critical care - Muhammad Naufal, Mansor; Sazali, Yaacob, Prof. Dr.; Nagarajan, Ramachandran, Prof. Dr. (Science Academy Publisher, 2011)
Link to publisher's homepage at http://sciacademypublisher.com/